Medium-scale resonant wave barrier for seismic surface waves. Issue 8 (13th October 2021) - Zeighami, Farhad; Palermo, Antonio; Vratsikidis, Athanasios; Cheng, Zhibao; Pitilakis, Dimitris; Marzani, Alessandro
Abstract: In this work, we design an experimental campaign to assess the attenuation performance of a medium-scale resonant wave barrier operating within the frequency range of 50–100 Hz. In particular, the dispersive properties of (i) bare soil, (ii) a configuration of "dead masses" placed over the soil surface, and (iii) a locally resonant barrier, also known as metabarrier, are compared numerically. The resonant barrier introduces a significant amplitude reduction of the surface waves in a narrow frequency range around the resonant frequency of the resonators. Multiple-frequency barriers are designed with increasing and decreasing resonant frequencies to enlarge the attenuation frequency band.